Dealing with dichotomies: Economic and innovative capacity on Bornholm - Lisa Van Well (European Regional Science Association (ERSA), 2010)
This paper aims to characterise the interplay between regional development and economic and innovative capacity on the Danish island community of Bornholm. Drawing on studies of institutions, innovative capacity is highlighted as knowledge resources, relational resources and mobilisation capacity. Building on these concepts, the institutions of regional development on Bornholm are examined in terms of how traditional core competencies in agriculture and the fishing industries are being utilised and are in the process of change towards a new core competency. The study shows how knowledge resources on Bornholm appear to be sufficient for fostering regional development in new endeavours. Bornholm is also working hard to facilitate new relationships and social capital to build innovative capacity. But the mobilisation of visions and goals towards a new core competency is being hindered by to the social and institutional dichotomies on the island. These dichotomies are examined in the paper and examples are presented of how Bornholm is currently dealing with this situation.
Keywords: 330